2017
DOI: 10.1111/dme.13531
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors at hospital admission and discharge in Type 1 and 2 diabetes

Abstract: Medication reconciliation identified medication errors in one third of individuals. Clinical pharmacists should focus on poly-medicated individuals, but also on other high-risk people, for example, those with Type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
2
13
0
1
Order By: Relevance
“…The noted proportion of discharge summaries with medication discrepancies, with regard to the pharmacist-compiled admission medication list as well as medication changes and adjustments during hospitalisation according to hospital electronic medical records, were in accordance with an American study noting one or more discharge medication errors for 39% of the patients [7], as well as a Canadian study noting a matching discrepancy occurrence 30 days post-discharge [14]. A somewhat lower proportion of 29% of diabetic patients having at least one error at admission and/ or discharge was noted in a French study [12]. In contrast, other European studies have shown considerably higher rates of medication discrepancies or inconsistencies in discharge documents [11,26], and a recent Australian study noted one or more medication discrepancies in more than half of the electronic discharge summaries [15].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The noted proportion of discharge summaries with medication discrepancies, with regard to the pharmacist-compiled admission medication list as well as medication changes and adjustments during hospitalisation according to hospital electronic medical records, were in accordance with an American study noting one or more discharge medication errors for 39% of the patients [7], as well as a Canadian study noting a matching discrepancy occurrence 30 days post-discharge [14]. A somewhat lower proportion of 29% of diabetic patients having at least one error at admission and/ or discharge was noted in a French study [12]. In contrast, other European studies have shown considerably higher rates of medication discrepancies or inconsistencies in discharge documents [11,26], and a recent Australian study noted one or more medication discrepancies in more than half of the electronic discharge summaries [15].…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, a Swedish study of elderly patients with many drugs showed, on average, two medication errors in every care transition [3]. Drug omission is the most common discrepancy and error type according to several studies [9][10][11][12]. The number of medications as well as increasing age seem to increase the discharge document medication discrepancy and error rate [11,14].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…35, 824 (2018) Breuker et al [1] highlighted that patients with Type 1 diabetes have an approximately twofold higher risk of medication errors at hospital admission compared with those with Type 2 diabetes. Med.…”
mentioning
confidence: 99%
“…Med. 35, 824 (2018) Breuker et al [1] highlighted that patients with Type 1 diabetes have an approximately twofold higher risk of medication errors at hospital admission compared with those with Type 2 diabetes. There are certain differences in the pathophysiology of the two types of diabetes that need to be considered during diabetes care at hospitals.…”
mentioning
confidence: 99%